Identification of Strategic Project Management Resources in Indian Software Project Management Companies - Mishra, Rakesh K. (Prabandhan: Indian Journal of Management, 2015)
This paper presents identification of strategic resources for software project management companies. Furthermore, the paper also identified the factors that attained VRIO characteristics amongst these resources. The research used primary data collected from professionals working in Indian software project management companies through a survey instrument. Factors were identified among the variables to identify the resources as well as identification of resources attaining VRIO characteristics. The findings resulted into identification of six important groups of resources and four factors pertaining to VRIO characteristics. The study may help software project companies to enhance their performance from a strategy perspective.